CONSUMER ANALYSIS IN THE USE OF TOURISM TRANSPORTATION FACILITIES THROUGH PROMOTIONAL BY TOURIST FACTORS AT PT. KISWAH MULYA SEJAHTERA CIREBON - Nunung Nurnilasari; Sarifudin Sarifudin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to expose the promotion implementation and consumer development in using tourism transportation facilities and determine the relationship between promotion and consumer behavior in using tourism transportation facilities. This research’s novelty lies in reviewing the use of tourism transportation facilities associated with promotional aspects from the consumer's perspective. The research method used was descriptive verification. The descriptive method itself is a research method to make an overview of existing situations or events so that this method is held for data accumulation. Meanwhile, the basis of verification is to assess the correctness of data collection in the field. The sample employed was Slovin’s formula. Then, the data collection techniques utilized were literature and field research to obtain primary data through interviews and questionnaires and secondary data in the form of existing documents. Based on the results of processing the questionnaire data, which were then analyzed using the Pearson Correlation Product Moment formula, it was obtained that the correlation coefficient between promotion and consumer behavior in the use of tourism transportation facilities was 0.720 and belonged to the category of solid relationship level. The coefficient of determination of 51.8% also indicates that promotions influenced consumers by 51.8%, while other factors affected consumer behavior by 100% - 51.8% = 49.2%. From the study results, t-count = 10.06 was higher than t-table = 1.986, with an error rate of 5%, rejecting the null hypothesis (H0) and accepting the alternative hypothesis (Ha). It suggests that the correlation coefficient obtained from the analysis could be applied to the population. Moreover, linear regression produced the equation Y = 10.84 + 0.74 X, implying that if the X value is increased by one unit, the Y value will increase by 0.74 at a constant level of 10.84.